2020
DOI: 10.5937/gp24-28226
|View full text |Cite
|
Sign up to set email alerts
|

On the perpetuation and contestation of racial stigma: Urban Roma in a disadvantaged neighbourhood of Szeged

Abstract: Stigmatisation of Roma people has long received attention in the academic literature but the internalisation of stigma among segregated urban Roma has been little researched. By adopting a theoretical perspective on collective identity and (urban Roma) racial stigmatisation, this paper aims to 1) understand the broader nature of urban Roma stigmatisation maintained by the non-Roma people and among the Roma, and 2) better position the internalisation of stigma and the burden of Roma stigmatisation. The paper us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 42 publications
0
27
0
1
Order By: Relevance
“…Green innovation is a powerful tool to break through the constraints of resources and the environment and facilitate the sustainable development of enterprises [72]. Remus et al [73] found that state-owned public property company (IKV) of Hungary provided unfair housing prices to poor Roma, which aggravated their poverty and was not conducive to the long-term development of the state economy. The government energetically deepens SOE reform to strengthen market-oriented construction, perfect the regulatory mechanism of environmental legality, encourage enterprises to assume environmental responsibility, spontaneously carry out green transformation, and release institutional bonuses for improving poverty alleviation, so as to propel the sustainable development of enterprise and country.…”
Section: Additional Analysis: Heterogeneity Test Of Industry Attribute and Marketization Degreementioning
confidence: 99%
“…Green innovation is a powerful tool to break through the constraints of resources and the environment and facilitate the sustainable development of enterprises [72]. Remus et al [73] found that state-owned public property company (IKV) of Hungary provided unfair housing prices to poor Roma, which aggravated their poverty and was not conducive to the long-term development of the state economy. The government energetically deepens SOE reform to strengthen market-oriented construction, perfect the regulatory mechanism of environmental legality, encourage enterprises to assume environmental responsibility, spontaneously carry out green transformation, and release institutional bonuses for improving poverty alleviation, so as to propel the sustainable development of enterprise and country.…”
Section: Additional Analysis: Heterogeneity Test Of Industry Attribute and Marketization Degreementioning
confidence: 99%
“…According to studies by Bouzarowski, 64.5% of Bulgarian households in 2010 were unable to keep their home "sufficiently warm", while 32.1% said they had arrears in paying for utilities [1]. Energy poverty, and thus difficult housing conditions, insufficient heating of the apartment or the lack of access to electronic devices, may be one of the many reasons for the stigmatization of certain national and social groups, such as Romani people living in many countries, e.g., Hungary or Romania [26,27].…”
Section: Definition Of the Energy Poverty Phenomenon And Methods Of Its Measurementmentioning
confidence: 99%
“…The authors argued that some cities, for instance in Central Europe, could not become smart cities because they still have problems with the social inclusion of marginal people. In the near future, the issues of exclusion and contesting racial stigma of Romanies in many European cities must also be addressed [18] and it is necessary to plug stakeholders in by setting up a complex, multi-stakeholder, city-regional urbanity as a way toward real smartness in cities and regions [19]. The long list of challenges that city authorities have to face also includes the fight against corruption and negligence in urban management [20], the challenges of sustainable development, green cities, and, above all, liveable cities [21].…”
Section: Literature Reviewmentioning
confidence: 99%